TEACHING LANGUAGE AND LITERATURE: IN THE CONSTRUCTION OF KNOWLEDGE - Marques dos Santos, Rosália (Revista Gênero e Interdisciplinaridade, 2023)
This chapter deals with the guidelines that the PCN present for the teaching of the Portuguese language in basic education. They are important official reflections with regard to educational practices at school. Some tensions that the modern world faces are discussed, among which the tension between the global and the local is highlighted, which I seek to explore in the research, in addition to the need to build an intelligent space in the school, transforming it into a headquarters space. for knowledge and discoveries, where the student can build knowledge in an environment that stimulates creativity and curiosity in a productive way.